Strategi Respon atas Digitalisasi Bisnis pada Perempuan Pelaku Usaha Mikro dan Kecil - Nasution, Yasmine; Pramesti, Muthia (JURNAL SOSIAL HUMANIORA (JSH), 2024)
Institutional theory highlights that organizational success relies not only on resource availability but also on acceptance within its environment. Institutional isomorphism refers to the tendency of organizations within the same industry to adopt similar structures and strategies due to shared environmental pressures. In the context of micro and small enterprises (MSEs), digitalization has become a pivotal factor influencing business processes. Female MSEs exhibit diverse responses to digitalization, driven by the COVID-19 pandemic and market demands to enter digital commerce. This study investigates the strategies female MSEs employ to adapt to digital technology. Using a qualitative approach, in-depth interviews were conducted in September 2022 with female MSEs in Depok. The findings reveal that normative and mimetic isomorphism are dominant strategies, while coercive isomorphism is absent. Challenges in adopting digitalization stem from both personal and external factors. Despite these obstacles, female MSEs recognize the significance of digitalization for business sustainability. To address adaptation issues, many rely on support from family and community networks, facilitating the integration of digital tools into their operations. This collaborative approach underscores the importance of social support in overcoming barriers to digital transformation within MSEs.